Islamic Financial Literacy, Promotion, and Brand Image Towards Saving Intention in Sharia Bank - Rozikin, Achmad Zainul; Sholekhah, Irmadatus (Ekonomi Syariah IAIN Kudus, 2020)
This paper aims to empirically examine the relationship between Islamic financial literacy, promotion, and brand image and the intention of saving in Islamic banks. The data in the study were taken from 125 respondents. Respondents in this study were customers of Islamic banks, conventional banks, and were not yet customers of the two banks. This study uses quantitative research methods and analyzes the data using multiple regression models with SPSS 21 application. The results indicate that Islamic financial literacy, promotion, and brand image affect the intention to save in Islamic banks.